Study on the Allowable Exposure Time of Temporary Goaf in the Open Stope and Backfill Mining Method with Large Structure Parameters - Xiaosheng Liu; Weijun Wang; Yizhong Luo; Jin Zhan (Advances in Civil Engineering)
Based on the uniaxial rheological experiment data of iron ore rock mass and filling body in large-scale stope obtained by using the rock servo controlling creep equipment, the characteristics of the creep curve were analyzed. The creep models of iron ore and filling body which can show the attenuation creep of rock were constructed. And a nonlinear creep model was obtained. According to the rheological data of the iron ore and the filling body, the parameters of the new nonlinear creep model were identified to obtain the material parameters of the creep model. Then, the creep model parameters were fitted and reduced to calculate the reasonable exposure time of temporary goaf in the large-scale stope. The results show that the reasonable exposure time of stope is 520 ～ 650 days, and the reasonable exposure time of filling body is 410 ～ 520 days. The model can well describe the initial attenuation creep stage and steady creep stage in the creep curve, which proves the correctness and rationality of the model. The study provides a reference for mining design and safety production of similar mines with large-scale stope structure.